Religious Piety and Sexual Passion: What Is the Connection?. Issue 3 (1st April 2022) - Clarke, Rebecca W.; Leavitt, Chelom E.; Busby, Dean M.
Abstract: The association between religiosity and the construct of sexual passion was examined to see whether religiosity is associated with harmonious, inhibited, and obsessive sexual passion styles. Using multiple regression and checking for interactions between religiosity, gender, broad categories of religion (Catholic, other Christian, other religious, nonreligious), and the three sexual passion styles, the following associations were found: Religiosity had a significant curvilinear relationship to all three sexual passion styles, suggesting an overlap in levels of religiosity and the construct of sexual passion. Optimal sexual passion outcomes were found at both higher and lower levels of religiosity, whereas mid-level religiosity was associated with the less beneficial sexual passion outcomes. Religious men were significantly more obsessively passionate than religious women, and religious men and women were similarly high on levels of harmonious and low on inhibited sexual passion. There were no significant interactions between religiosity, broad categories of religion, and sexual passion styles. Understanding how religion and sexual passion are associated could be useful for applied researchers as well as those who work with religious individuals who want to help these individuals develop beneficial patterns of sexual passion.